Outcome of transcatheter aortic valve replacement in bicuspid aortic valve stenosis with new-generation devices. (17th November 2020) - Gorla, Riccardo; Casenghi, Matteo; Finotello, Alice; De Marco, Federico; Morganti, Simone; Regazzoli, Damiano; Bianchi, Giovanni; Acerbi, Elena; Popolo Rubbio, Antonio; Brambilla, Nedy; Testa, Luca; Castriota, Fausto; et al.
Abstract: OBJECTIVES: To compare device success and paravalvular leak rates of 3 new-generation transcatheter aortic valve replacement devices in patients with bicuspid aortic valve stenosis and to test their biomechanical performance in a computer-based simulation model of aortic root with increasing ellipticity. METHODS: This retrospective multicentre study included 56 bicuspid aortic valve patients undergoing transcatheter aortic valve replacement with new-generation devices: Lotus/Lotus Edge ( N = 15; 27%), Evolut-R ( N = 20; 36%) and ACURATE neo ( N = 21; 37%). Three virtual simulation models of aortic root with increasing index of eccentricity (0–0.25–0.5) were implemented. Stress distribution, stent–root contact area and paravalvular orifice area were computed. RESULTS: Device success was achieved in 43/56 patients (77%) with comparable rates among Lotus (87%), Evolut-R (60%) and ACURATE neo (86%; P = 0.085). Moderate paravalvular leak rate was significantly lower in the Lotus group as compared to Evolut-R group (0% vs 30%; P = 0.027) and comparable to the ACURATE neo group (0% vs 10%; P = 0.33). By index of eccentricity = 0.5, Lotus showed a uniform and symmetric pattern of stress distribution with absent paravalvular orifice area, ACURATE neo showed a mild asymmetry with small paravalvular orifice area (1.1 mm 2 ), whereas a severely asymmetric pattern was evident with Evolut-R, resulting in a large paravalvular orifice area (12.0 mm 2 ). CONCLUSIONS: Transcatheter aortic valve replacement in bicuspid aortic valve patients with new-generation devices showed comparable device success rates. Lotus showed moderate paravalvular leak rate comparable to that of ACURATE neo and significantly lower than Evolut-R. On simulation, Lotus and ACURATE neo showed optimal adaptability to elliptic anatomies as compared to Evolut-R.